2021
DOI: 10.1007/s10533-021-00784-w
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater salinization syndrome: from emerging global problem to managing risks

Abstract: Freshwater salinization is an emerging global problem impacting safe drinking water, ecosystem health and biodiversity, infrastructure corrosion, and food production. Freshwater salinization originates from diverse anthropogenic and geologic sources including road salts, human-accelerated weathering, sewage, urban construction, fertilizer, mine drainage, resource extraction, water softeners, saltwater intrusion, and evaporative concentration of ions due to hydrologic alterations and climate change. The complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
111
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(111 citation statements)
references
References 246 publications
(325 reference statements)
0
111
0
Order By: Relevance
“…Similarly, Leslie and Lyons ( 2018 ) attributed a winter‐time spike of chloride concentrations in Columbus, Ohio tap water to the application of roadway deicing agents. Furthermore, winter‐time seasonal peaks in sodium and/or chloride concentrations have also been observed in surface water bodies used for drinking water purposes throughout the northeastern and midwestern United States (Dailey et al., 2014 ; Kaushal et al., 2018 , 2021 ; Kelly et al., 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Leslie and Lyons ( 2018 ) attributed a winter‐time spike of chloride concentrations in Columbus, Ohio tap water to the application of roadway deicing agents. Furthermore, winter‐time seasonal peaks in sodium and/or chloride concentrations have also been observed in surface water bodies used for drinking water purposes throughout the northeastern and midwestern United States (Dailey et al., 2014 ; Kaushal et al., 2018 , 2021 ; Kelly et al., 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mass loss estimation excluded the leaching period, which has been shown to be affected by salinity associated parameters [5,23] and there were no invertebrate shredders colonizing the leaves. We may thus assume that mass loss was mainly due to microbial degradation, and that the 61% lower mass loss in treatment 15.3 mS cm −1 was a result of decreased microbial activity on leaf litter.…”
Section: Leaf Litter Decomposition and Associated Invertebratesmentioning
confidence: 99%
“…How freshwater organisms and ecosystem processes will respond to the increasing salinization of coastal freshwaters, predicted by the Intergovernmental Panel on Climate Change [1], is a fundamental quest for an integrated biodiversity and conservation management of coastal ecosystems at risk. Studies on a wide variety of lakes, rivers, and wetlands have shown salinity effects on freshwater organisms and on ecosystem structure and function [3][4][5][6]. Regarding freshwater animals, salinity may have lethal effects once a threshold is exceeded, or sub-lethal effects, reducing both organism and population fitness, and resulting in the decline of richness with increasing salinity [3,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing mineral dissolution and salinity can enhance the mobility of Ra by introducing competing or complexing ions . Studies in coastal regions experiencing seawater intrusion have shown that Ra concentrations correlate positively with salinity. , Outside of coastal areas, salinization of fresh water has been attributed to long-term applications of road salt, which also has been reported to mobilize Ra. , We use the term “road salt” to indicate rock salt and brine used for road-deicing and anti-icing. Rock salt (halite, NaCl) used for road applications can include minor amounts (∼10 g/kg) of Mg and Ca with trace amounts (<50 mg/kg) of Ba and Sr. , Salt brines used for anti-icing may also contain mixtures of NaCl, CaCl 2 , and MgCl 2 .…”
Section: Introductionmentioning
confidence: 99%